Exploring the Impact of Intermittent Fasting on Metabolic Syndrome, Prediabetes and Type 2 Diabetes: a systematic review - Kosieradzka, Karolina; Kosecka, Katarzyna; Rudziński, Patryk; Cieślik, Aleksandra; Adamowicz, Dominik; Stańczyk, Justyna; Łopuszyńska, Inga; Meliksetian, Astrik; Wosińska, Alicja; Jargieło, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Metabolic syndrome, prediabetes and type 2 diabetes mellitus represent a growing and interconnected health challenge, gaining significant attention due to their high prevalence and impact they have on individuals' well-being. Intermittent Fasting (IF), involving cycling between periods of fasting and eating, has emerged as a promising dietary approach garnering substantial attention for its potential therapeutic effects on metabolic health. Purpose: This review aims to explore the impact of intermittent fasting on metabolic disease by examining recent studies. Methods: A review of the recent literature was conducted to explore potential positive effects of IF on relevant metabolic parameters. Results: The findings from the reviewed studies demonstrated favorable effects of IF associated with improvements in glycemic control as improved insulin sensitivity and decreased HbA1c levels. Additionally, it led to significant reductions in body weight and waist circumference. Beneficial effects on lipid profiles, such as reduced triglyceride levels, were also observed in some studies. Conclusions: The reviewed studies provide strong evidence supporting the effectiveness of IF regimens in improving metabolic factors, including weight, insulin sensitivity and lipid profiles in individuals with abnormal glucose metabolism. IF offers a promising dietary strategy potentially providing additional benefits beyond conventional dietary interventions. However, further research is needed to elucidate the long-term effects, optimal fasting protocols and potential mechanisms underlying the benefits of intermittent fasting in these conditions.